2020
DOI: 10.18805/ijar.b-3727
|View full text |Cite
|
Sign up to set email alerts
|

F Gene and N Gene based Reverse Transcription PCR for Molecular Characterization of Peste des Petits Ruminants Virus

Abstract: Present investigation was undertaken to detect and characterize the PPR virus from different clinical tissue samples of 14 sheep and 17 goats with respiratory disease from Maharashtra, India. All animals were tested by Sandwich ELISA, of which 70.96% were found positive carrying high PPR virus inwhich 12 were sheep and 10 were goats respectively. For confirmation of PPR, molecular detection was performed with RT-PCR using F gene and N gene specific primers. Intestine samples accounted for highest percent posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Out of 200 samples of nasal swab, tracheal swab, lungs and lung associated lymphnodes collected from 50 carcasses; twenty carcasses were found to be affected by PPR virus. PPRV antigen was detected equally i.e (100%) in nasal swab, tracheal swab, lung associated lymph nodes and lungs of eleven goats and nine sheep respectively (Pandey et al 2020). Similar study was conducted on different clinical samples of small ruminants (Mahajan et al 2012) for detection of PPR antigen which revealed lung and nasal swabs are more appropriate for detection of PPR antigen.…”
Section: Detection Of Pprv Antigenmentioning
confidence: 59%
“…Out of 200 samples of nasal swab, tracheal swab, lungs and lung associated lymphnodes collected from 50 carcasses; twenty carcasses were found to be affected by PPR virus. PPRV antigen was detected equally i.e (100%) in nasal swab, tracheal swab, lung associated lymph nodes and lungs of eleven goats and nine sheep respectively (Pandey et al 2020). Similar study was conducted on different clinical samples of small ruminants (Mahajan et al 2012) for detection of PPR antigen which revealed lung and nasal swabs are more appropriate for detection of PPR antigen.…”
Section: Detection Of Pprv Antigenmentioning
confidence: 59%
“…All the samples were screened PCR positive (Fig 3) for PPRV. Molecular based confirmation for PPR virus is the most reliable and extensively used technique for diagnosis due to its high sensitivity and specificity (Kumar et al 2014;Pandey et al 2020).…”
Section: Molecular Confirmation By Pcrmentioning
confidence: 99%